2021
DOI: 10.1111/cns.13637
|View full text |Cite
|
Sign up to set email alerts
|

A bioisostere of Dimebon/Latrepirdine delays the onset and slows the progression of pathology in FUS transgenic mice

Abstract: Aims To assess effects of DF402, a bioisostere of Dimebon/Latrepirdine, on the disease progression in the transgenic model of amyotrophic lateral sclerosis (ALS) caused by expression of pathogenic truncated form of human FUS protein. Methods Mice received DF402 from the age of 42 days and the onset of clinical signs, the disease duration and animal lifespan were monitored for experimental and control animals, and multiple parameters of their gait were assessed throughout the pre‐symptomatic stage using CatWalk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Our study has revealed the presence of an increased sensitivity of microglia to inflammatory challenges at in early pre-symptomatic stages of the ALS/FTLD-like syndrome in mice with compromised FUS function. It is accompanied by elevated CNS cytokine production under unchallenged conditions and is present prior any signs of neurodegeneration in FUS-tg mutants ( de Munter et al, 2020b ; Chaprov et al, 2021 ), thus suggesting these pro-inflammatory processes are independent of neuronal cell death. Finally, the FUS[1–359]-tg mouse line used here can be a useful model to address the role of microglia and inflammation in the mechanisms of ALS/FTLD syndrome further.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study has revealed the presence of an increased sensitivity of microglia to inflammatory challenges at in early pre-symptomatic stages of the ALS/FTLD-like syndrome in mice with compromised FUS function. It is accompanied by elevated CNS cytokine production under unchallenged conditions and is present prior any signs of neurodegeneration in FUS-tg mutants ( de Munter et al, 2020b ; Chaprov et al, 2021 ), thus suggesting these pro-inflammatory processes are independent of neuronal cell death. Finally, the FUS[1–359]-tg mouse line used here can be a useful model to address the role of microglia and inflammation in the mechanisms of ALS/FTLD syndrome further.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies with the FUS[1–359]-tg mice revealed that the pathology is associated with over-expression of the pro-inflammatory cytokines IL-1β and IL-6 in the brain, blood and spinal cord, and behavioural deficits in the symptomatic FUS[1–359]-tg mice ( de Munter et al, 2020a , 2020b ; Probert et al, 2022 ; Lysikova et al, 2019 ). However, gene expression studies failed to reveal any signs of altered microglial function or of inflammatory markers in the CNS of naïve pre-symptomatic FUS[1–359]-tg mice ( Chaprov et al, 2021 ). Here, we studied immunohistochemical expression of Iba-1 in the prefrontal cortex (PFC), hippocampus (HIP) and spinal cord (SC) of naïve pre-symptomatic 8-week old FUS[1–359]-tg mice 24 h after an LPS injection.…”
Section: Introductionmentioning
confidence: 99%
“…The rotarod test, foot‐fault test, CatWalk gait analysis, novel object recognition test, and open‐field test were performed according to a previously described protocols. 43 , 44 , 45 , 46 The balance ability of mice was assessed using a rotarod apparatus (Ugo Basile). The average latency time of three trials to fall off the rotating rod was recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, motor deficits have been successfully identified through gait analysis in other ALS mouse models, demonstrating the versatility of this approach in studying the disease. For example, gait analysis has been applied to transgenic mouse models induced by the expression of pathogenic truncated forms of the human FUS (fused in sarcoma) gene 34 or by transgenic mice expressing full-length hTDP-43 under the control of the mouse prion promoter. 32 These findings further highlight the utility of gait analysis as a valuable tool for characterizing motor defects in various ALS models, contributing to our understanding of the disease and potential therapeutic interventions.…”
Section: Gait Analysismentioning
confidence: 99%